Transformational leadership as a mediator of the influence of digital workplace and digital culture on employee engagement (Evidence from the Indonesian public sector) - Maulana Maulana; Tien Yustini (Jurnal Mantik, 2026)
Digital transformation is a strategic priority for public sector performance, yet employee engagement among Indonesian Civil Servants (ASN) remains low. This study examines the impact of digital workplace and digital culture on employee engagement, with transformational leadership as a mediating variable, among 399 Civil Servants in the South Sumatra Provincial Government. Utilizing a quantitative explanatory design with proportionate stratified random sampling, data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that both digital workplace and digital culture significantly and positively influence employee engagement and transformational leadership. Furthermore, transformational leadership partially mediates these relationships. These findings demonstrate that digital initiatives are most effective when supported by leadership that fosters collaboration and innovation. This study offers an empirically validated model for public sector engagement and provides actionable guidance for policymakers advancing bureaucratic reform